2018
DOI: 10.1016/j.amjmed.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Headache

Abstract: Headache, an almost universal human experience, is one of the most common complaints encountered in medicine and neurology. Described and categorized since antiquity, with the first classification by Aretaeus of Cappadocia, other classifications followed. The evaluation of this condition may be straightforward or challenging, and, though often benign, headache may prove to be an ominous symptom. This review discusses the current diagnosis and classification of headache disorders and principles of management, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
76
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 51 publications
2
76
0
9
Order By: Relevance
“…Headache is one of the most frequent complaints in primary care practices and a very common condition reported by children, adolescents, and young adults [ 1 , 2 , 3 , 4 ]. However, headache phenotypes differ depending on the age group.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Headache is one of the most frequent complaints in primary care practices and a very common condition reported by children, adolescents, and young adults [ 1 , 2 , 3 , 4 ]. However, headache phenotypes differ depending on the age group.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that 93% of the analyzed children presented a recent onset of headache, whereas medium- and late-onset headaches were reported by 3% and 4% of all patients, respectively [ 5 ]. The overall headache prevalence has been reported to be as high as 56% in children under 10 years of age and 91% in early adulthood [ 3 , 6 ]. Additionally, a relationship between gender and the frequency of headaches was observed in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tricyclic antidepressant amitriptyline is recommended for patients who have both CTTH and anxiety. [13][14][15] Nonpharmacologic treatments are generally included in clinical guidelines for the prevention of primary headaches. The European Federation of Neurological Societies guideline, 16 the Italian guideline for primary headaches, 17 in patients with CTTH is based on the high prevalence of musculoskeletal dysfunctions [19][20][21][22] and on the role of affective and social touch in pain modulation.…”
mentioning
confidence: 99%